2015
DOI: 10.3238/arztebl.2015.0195
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality, Stroke, and Coronary Events

Abstract: SUMMARYBackground: Studies have shown that air pollution is associated with cardiopulmonary mortality, but there has been less research of the possible effect of air pollution on stroke and non-fatal coronary events. The Heinz Nixdorf Recall (HNR) study addressed the question of the effect of long-term air pollution on stroke and coronary events. Ambient acoustic noise was also considered as a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
(53 reference statements)
3
30
0
Order By: Relevance
“…Model covariates were chosen a priori and included age, sex, race, body mass index (BMI), smoking status, comorbidities (diabetes, COPD, hypertension, hyperlipidemia), hypertensive medication use, statin medication use, and neighborhood socioeconomic status (SES) at the block-group level. Covariates were selected on the basis of plausibility and previously published relationships [ 2 , 12 , 13 ]. Individual-level covariates and pharmacy data were obtained from electronic medical records.…”
Section: Methodsmentioning
confidence: 99%
“…Model covariates were chosen a priori and included age, sex, race, body mass index (BMI), smoking status, comorbidities (diabetes, COPD, hypertension, hyperlipidemia), hypertensive medication use, statin medication use, and neighborhood socioeconomic status (SES) at the block-group level. Covariates were selected on the basis of plausibility and previously published relationships [ 2 , 12 , 13 ]. Individual-level covariates and pharmacy data were obtained from electronic medical records.…”
Section: Methodsmentioning
confidence: 99%
“…A 2015 study by Hoffmann et al, demonstrated that long-term exposure to PM is associated with an increased risk of stroke, regardless of the subject’s exposure to noise. [85] However, another study that adjusted for these variables found road traffic noise is associated with ischemic stroke, while air pollution is not. Further investigations are needed.…”
Section: Air Pollution and Strokementioning
confidence: 99%
“…However, in those participants with no or only minor atherosclerotic burden at baseline, we observed associations of long-term exposure to Environmental Health Perspectives 107003-4 128(10) October 2020 particulate air pollution with progression of atherosclerosis, whereas estimated effects in the group with more advanced atherosclerotic burden at baseline were null or inverse. Long-term air pollution has been shown to be associated with cerebrovascular and cardiovascular events in multiple studies (U.S. EPA 2019; WHO 2013), including prior analyses of the HNR Study (Hoffmann et al 2015). Therefore, our findings are important regarding the underlying hypothesis that ambient air pollution may lead to atherosclerosis on the pathway to CVD, possibly explaining the higher incidence and prevalence of cardiovascular and cerebrovascular disease observed in people with higher air pollution exposure.…”
Section: Discussionmentioning
confidence: 75%